Innovation, design, and social sustainability: New trends for local development in the contemporary world - Martinez-Osorio, Pedro Arturo [UNESP]; Barana, Marcia [UNESP]; Rocha-Carneiro, Rodrigo [UNESP]; Paschoarelli, Luis Carlos [UNESP] (Univ Catolica Colombia, Fac Psicologia, 2017)
This paper takes as its point of departure the counter-currents envisioned by Gui Bonsiepe in 1978 regarding the practice of design. The development of these ideas is reviewed based on the evolution of the concept of sustainability, as well as its social approach and relationship with innovation and design. In line with Bonsiepe's ideas, the paper identifies changes in the role of design in order to meet new social needs; as examples, it presents interventions based on participatory design and social innovation, which generate alternatives for local development in the contemporary city. Due to new realities, the ability to construct intangible products is ever more important. The political action of design is more and more urgent; designers are called to play a leading role in the critical construction of new citizenship identities. A new field of action: social design.
Keywords: Design; participatory design; social innovation; sustainability